SOME OF PHENOTYPIC, PHYSICAL AND ANATOMICAL WOOD PROPERTIES OF VALONIA OAK TREES IN KURDISTAN-IRAQ - & et al., Aree (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2021)
This study was aimed to investigate the morphologic, macroscopic, and microscopic description with the paper pulp quality index was determined to facilitate its increased use and to analyze the variation of wood properties. Among different morphological characteristics Q. aegilops registered mean height (13.63 m) and diameter (26.04 cm), while bark thickness represented from 7.2 to 15.6mm. Average bark and wood percent was noticed (8.22%) and (91.78%) of the total volume, with annual ring growth width (3.17mm) that considered a slow-growing species. The highest heartwood proportion of stem volume was 75.32% and the lowest 42.01% with a mean of 61.46%. The sapwood proportion ranged between 23.68 and 57.99% with a mean of 38.54%. While the values of anatomical properties were: The mean values of fiber length, fiber diameter, double cell wall thickness, and fiber lumen width were 1.01mm, 15.54µm, 6.288µm, and 9.25µm respectively. Moreover, the mean values of vessel length and vessel diameters were 0.54mm and 179.80µm respectively. Significant differences were found in the pulpwood quality indices for the paper samples, the means value of the runkel index was 0.86, while, slenderness index was 68.84, the coefficient of flexibility was 0.57, and the average value of the stiffness coefficient was 0.421. The fibers length more than1mm and cell well is thick accordingly are classified as good for paper. Based on its morphological and physical properties, Q. aegilops wood can be used in various wood manufactures. Based on the anatomical properties and pulp quality indices, this wood could be used to obtain cellulose pulp for paper production.